Effects of Investor-State Dispute Settlements (ISDS) on Foreign Direct Investment (FDI) Flows - Frans Lavdari; Xhulio Lavdari (Policy Perspectives)
This paper assesses how ISDS mechanisms have impacted FDI flows, using quantitative data from more than 100 countries between 2000 and 2020. By applying a differences-in-differences approach combined with a gravity model, it finds that ISDS disputes immediately reduce FDI because of the uncertainty created. At the same time, favorable awards to investors produce a strong, long-term investment rebound. Sectoral and regional imbalances have been underlined, with extractive industries and developing regions even more adversely affected. Findings like these raise some concerns about the ‘chilling effect’ on state regulatory autonomy and imply the need for reform of ISDS to strike a balance between investor protection and public policy objectives.